Problematic Social Situations for Peer-Rejected Students in the First Year of Elementary School - Martín-Antón, Luis J.; Monjas, María Inés; García Bacete, Francisco J.; Jiménez-Lagares, Irene (Frontiers in Psychology, 2016)
This study examined the social situations that are problematic for peer-rejected students in the first year of elementary school. For this purpose, exploratory and confirmatory factor analyses were conducted on the Taxonomy of Problematic Social Situations for Children (TOPS, Dodge et al., 1985) in 169 rejected pupils, identified from a sample of 1457 first-grade students (ages 5-7) enrolled in 62 classrooms of elementary school. For each rejected student, another student of average sociometric status of the same gender was selected at random from the same classroom (naverage = 169). The model for the rejected students showed a good fit, and was also invariant in the group of average students. Four types of situations were identified in which rejected students have significantly more difficulties than average students. They are, in descending order: (a) respect for authority and rules, (b) being disadvantaged, (c) prosocial and empathic behavior, and (d) response to own success. Rejected boys have more problems in situations of prosociability and empathy than girls. The implications concerning the design of specific programs to prevent and reduce early childhood rejection in the classroom are discussed.